Clinical characteristics and genetic mutations in hemophilia A patients with inhibitors - Fitri Primacakti; Pustika Amalia Wahidiyat; Damayanti Rusli Sjarif; Novie Amelia Chozie; Ninik Sukartini; Joedo Prihartono; Sheila Claudhea Salsabila; Nadhifa Tazkia Ramadhani; Bidasari Lubis (Paediatrica Indonesiana, 2026)
Background Antibodies to factor VIII, known as inhibitors, are a major problem in hemophilia A, especially in severe cases. Certain genetic mutations are associated with a higher risk of the formation of inhibitors. This study is the first in Indonesia to report on genetic mutations of hemophilia A patients with inhibitors. Objectives To detect genetic mutations, investigate potential risk factors, and evaluate inhibitor prevalence in pediatric hemophilia A patients. Methods An observational study was conducted at the Pediatric Hemophilia Treatment Center of Cipto Mangunkusumo Hospital, Jakarta. Inhibitors were measured using the Bethesda assay and classified as low- or high titer. Inverse shifting polymerase chain reaction (IS-PCR) was performed to detect inversion mutations. Negative results for inversion were followed by Sanger sequencing. Clinical data were obtained from medical records. Results Inhibitors were detected in 17 of 114 hemophilia A patients (14.9%), most of whom (88.2%) had severe disease and had fewer than 150 days of exposure to clotting factor concentrates (CFCs), classifying them as previously untreated patients (PUPs). The genetic mutations identified in inhibitor patients were intron 22 inversion (INV-22) mutations (41.2%), intron 1 inversion (INV-1) mutations (29.4%), nonsense mutations (17.6%), large deletions (5.9%), and missense mutations (5.9%). Family history of inhibitors, previous intensive treatment for major bleeding events or surgery, and type of concentrate were potential risk factors. Conclusion Intron 22 inversion mutations were the most common mutations associated with the presence of inhibitors in hemophilia A patients.